Penerapan Enterprise Resource Planning (ERP) pada Sistem Pembelian, Penjualan dan Inventory Barang di Mini Market 7 Putra - Andre Nofriandi; Husnil Kamil (Jurnal Nasional Teknologi dan Sistem Informasi, 2015)
7 Putra is one of the mini market located on the Pasar Sungai Sariak. Purchasing, sales, and inventory of goods on this market mini is done without using a computer. It can be seen from the process of buying new goods, the receipt of goods, payment to suppliers, inventories in storage, movement of goods, sales of goods and payments from customers. ll of the above processes suffer from the financial constraints and poorly controlled. Application development Enterprise Resource Planning (ERP) in a mini-market 7 Putra to assist and facilitate the process of purchase, sales and inventory items. Implementation of ERP in 7 Putra done through several stages of the business process analysis, analysis of ERP selection, ERP implementation and ERP testing. In filming the analysis of business processes, use BPMN (Business Process Modeling Notation). The module used in this research is the main module purchase, sales, as well as items and inventory. Before the implementation of ERP. ERP selection was done according to the 7th Round. The results of the election analysis showed FrontAccounting application is an application that is suitable for 7 Putra. ERP implementation is done by using the application FrontAccounting. System testing is done to check and make sure it is appropriate and ERP applications can run as expected. The test is based on existing business processes in 7 Putra. Results of testing ERP accordance with existing reporting and business processes in the 7th Round